A THREE-DIMENSIONAL KINEMATIC MODEL FOR THE DEFORMATION ABOVE AN ACTIVE DIAPIR - Yin H.; Groshong R.H. (My University, 2007)
This article presents the results of a finite-thickness, three-dimensional (3-D) kinematic model for the fault-related deformation above an active diapir. Based on field examples, the models are (1) circular in map view; (2) offset by radially distributed normal faults; (3) faulted or smooth at the top of the salt; (4) relatively unstrained on the flanks; and (5) highly deformed in the central graben, if present. Field examples suggest that active diapirs may initiate with either two or three master faults crossing near the dome crest. Subsequent evolution depends mainly on whether the master faults cut the salt or detach on the salt top. If the top of the salt is faulted, no minor faults are required except in the central graben. If the top of the salt is unfaulted, additional faulting occurs in the flank grabens. In models with three master faults, very different structural patterns appear in cross sections cut parallel and perpendicular to any of the master faults. The domes are asymmetrical in the fault-perpendicular cross sections, but are symmetrical in the fault-parallel cross sections. The initial fault pattern may influence the piercement efficiency. An active dome with faults offsetting the top of the salt grows more rapidly than a dome with a smooth top and may develop into a passive diapir more rapidly. The model map patterns are used to reinterpret the 3-D structure of the Clay Creek dome, Texas, and the Reitbrook dome, Germany. The model predictions are confirmed by the cross sections, and small, but potentially significant, refinements are proposed. Copyrigth ©2007. The American Association of Petroleum Geologists. All rights reserved.